Burnout and its subsequent impact on quality of care provided by nursing occupations in the long-term care sector: a scoping review protocol - Behdin Nowrouzi-Kia; Yiyan Li; Alexia M Haritos; Bao-Zhu Stephanie Long; Ali Bani-Fatemi; Aaron Howe (BMJ Public Health, 2025)
Introduction Individuals who work in the nursing sector play a crucial role in the healthcare system, yet those working in long-term care (LTC) facilities often face challenges and are at risk of burnout due to occupational factors such as workload. This burnout can affect their ability to provide optimal care to their residents. This scoping review protocol aims to understand the impact of burnout on the capacity to deliver high-quality care among nursing-related occupations in LTC settings.Methods and analysis A search will be conducted across Embase, CINAHL, Medline and APA PsycINFO. Studies will be included if they examine nursing professionals employed in the LTC sector, assess their experiences of burnout and explore how this burnout affects the quality of care they provide. No restrictions on publication year will be applied, and all study designs except knowledge syntheses will be considered. Eligible studies will be published in English or available in English translation. The study screening and data extraction will be completed by two independent reviewers. The included studies will undergo quality assessment using the Agency for Healthcare Research and Quality tool and the Newcastle-Ottawa Scale and the Critical Appraisal Skills Programme. A narrative synthesis approach will be used to report the findings.Ethics and dissemination Ethics approval and consent to participate are not applicable. A scoping review will be prepared by a research team at the University of Toronto following the protocol procedure. Subsequently, this manuscript will be prepared and submitted to a peer-reviewed journal to disseminate study findings to the research community and contribute to the growing field of nursing well-being research.